Anti-dumping - containment and reform - Bhat, T.P. (2004)
In the global trade policy discussions, the issue of anti-dumping has assumed significance. Many trade experts view that such a practice is trade disruptive. Increasingly, now, the anti-dumping instrument is used to protect non-competitive domestic industries against alleged "unfair trade" practices. It is an easy option for the governments to oblige domestic pressure groups to confirm favours. In the post-WTO era, anti-dumping actions have acquired menacing proportion denying market access achieved through successive GATT/WTO Trade Rounds. Anti-dumping Agreement is one of the contentious issues negotiated under the Uruguay Round. It achieved mixed results in tightening the rules that govern anti-dumping actions. The gains were introduction of de minimis and sunset review provisions. But loopholes were left in culmination provision, margin of dumping, material injury, cost calculation method, constructed value, initiation standard and termination provision and so on. The paper attempts to examine the salient features of the current anti-dumping agreement and traces its impact on international trade. It suggests ways and means to reform the rules to address genuine concerns of fair trade under the WTO framework. - Reproduced.
Keywords: International trade